ECOLOGICAL SAFETY OF CITIZENS OF RECREATIONAL ZONES OF THE BLACK SEA - Білявський, Г.; Голод, А. (Proceedings of National Aviation University (archive), 2012)
The article is devoted to meaningfulness estimation of ecological control of sea aquatory in forming ofsafety ecological conditions for citizens of the Black Sea. The pecularity and the role of technogenic pollution ofsea aquatory of the Black Sea are estimated. The degrees of ecological safety and negative influences of technogenicobjects on people living in the Black Sea coast are defined. The reccomendations for ecologization of recreationalzones of the Black Seat are characterized. The main goal of the work is the ecological estimation of livingconditions for sitizens in the Black Sea on the bases of using of methodology of complex searching andmarking of protecting laws